Antarctica’s Protected Areas Are Inadequate, Unrepresentative, and at Risk - Shaw, Justine D. (Public Library of Science, 2014)
Antarctica is widely regarded as one of the planet's last true wildernesses, insulated from threat by its remoteness and declaration as a natural reserve dedicated to peace and science. However, rapidly growing human activity is accelerating threats to biodiversity. We determined how well the existing protected-area system represents terrestrial biodiversity and assessed the risk to protected areas from biological invasions, the region's most significant conservation threat. We found that Antarctica is one of the planet's least protected regions, with only 1.5% of its ice-free area formally designated as specially protected areas. Five of the distinct ice-free ecoregions have no specially designated areas for the protection of biodiversity. Every one of the 55 designated areas that protect Antarctica's biodiversity lies closer to sites of high human activity than expected by chance, and seven lie in high-risk areas for biological invasions. By any measure, including Aichi Target 11 under the Convention on Biological Diversity, Antarctic biodiversity is poorly protected by reserves, and those reserves are threatened.